Concept, Design and Energy Performance of a Net Zero-Energy Building in Mediterranean Climate. (2016) - Ascione, Fabrizio; Bianco, Nicola; de Rossi, Filippo; Masi, Rosa Francesca De; Vanoli, Giuseppe Peter
Abstract: The paper shows boundary conditions, conceptions, design criteria and expected energy performance of a new net zero-energy building, designed for a typical Mediterranean climate and presently under construction in a middle-size city of South Italy. The single-storey building is the final outcome of an Italian project – SMARTCASE – promoted under the umbrella of the European Regional Development Fund. The building has been designed for being a best practice of a new way of living, by reducing - as much as possible - energy needs, energy demand of active energy systems and by converting the entire request by means of on-site renewables. Starting from the architectural concept, and thus shape, geometry and organization of the functions, as well as by considering the thermo-physical peculiarities of the thermal envelope – built in coated X-lam in order to allow both thermal resistance and thermal capacity - the conception phase has interested many professionals. Analogously, all active energy systems, and thus the heating, ventilating and air-conditioning devices, equipment for domestic hot water, artificial lighting and plugged powers are the top of the technology. In addition, a great effort has been dedicated to monitoring and controls. Moreover, the solar energy systems, the air-cooled heat pumps, the geothermal boreholes allow to close to zero the energy balance.